Predicting response to switching from phosphodiesterase type 5 inhibitor to riociguat in patients with pulmonary arterial hypertension: biomarker and responder analysis of the RESPITE and REPLACE studies - Klinger, James R.; Al-Hiti, Hikmet; Chang, Sung-A.; Chang, Hyuk J.; Ghofrani, Hossein-Ardeschir; Grünig, Ekkehard; Hoeper, Marius M.; Jansa, Pavel; Ota-Arakaki, Jaquelina; Pulido, Tomas; Simonneau, Gérald; Vizza, Carmine Dario; et al. (Pulmonary circulation, 2025)
This exploratory analysis assessed whether plasma biomarkers predict the response to switching from phosphodiesterase type 5 inhibitors (PDE5is) to the soluble guanylate cyclase stimulator riociguat in patients with pulmonary arterial hypertension. Selected biomarkers at baseline and their changes to Week 24 were evaluated in patients with and without a favorable response to riociguat in two trials: RESPITE, in which patients with an inadequate response to PDE5i were switched to riociguat; and REPLACE, in which patients at intermediate risk of 1-year mortality despite a PDE5i were randomized to remain on PDE5i or were switched to riociguat. A response was defined as absence of clinical worsening and at least two of the following criteria: 6-min walk distance increase by 10% or ≥ 30 m, World Health Organization functional class I/II, or N-terminal prohormone of brain natriuretic peptide reduction of ≥ 30% at Week 24. In REPLACE, responders had significantly higher baseline cyclic guanosine monophosphate (cGMP) and significantly lower baseline asymmetric dimethylarginine, and growth/differentiation factor 15 (GDF-15) than nonresponders. In RESPITE, responders had lower baseline GDF-15 than nonresponders, and nonresponders showed a significantly greater decrease in cGMP than responders. No baseline threshold value of any biomarker provided a good likelihood of predicting the response to riociguat. Overall, the biomarkers evaluated did not help to identify patients who were more likely to respond to switching from PDE5is to riociguat.